Linear Lichen and Anterior Cervical Hypertrichosis: Unusual Association (Archives of Clinical and Medical Case Reports, 2018)
Linear lichen planus is a rare variety of lichen planus characterized by lesions following the lines of Blaschko. Anterior cervical hypertrichosis is a rare and unrecognized form of local congenital hypertrichosis. It is characterized by the presence of a tuft of terminal hair on the anterior cervical region. We report an exceptional association of these two entities.